RUANG KREATIF KRAMAT - Bella Octavia Darmawan; Suryono Herlambang (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Urban life is synonymous with routine and high activity in which competition between individual communities continues to increase. The routine and busyness that continues to accumulate by each individual approves fatigue and demands less productive work / study. The third place is present to balance the lives of people outside the home and work place. That way, third place is needed in the big city area which is also adjusted to the needs of the community. This project supports the balance of life in the communities around the Kramat village, Senen with programs that suit their needs. The program that emerges according to the Kramat region is a creative space because the local residents who have a profession as ondel - ondel craftsmen but do not have a place to channel these talents.The design method includes data collection techniques through observation and interviews with the results applied to the transformation design method. Kramat Creative Place in Senen is the third place planned to serve the needs of the surrounding community in the social and creativity fields in order to address the issue of urban life due to daily busyness. This project provides several facilities that facilitate community activities in education, eating places, and meeting / socializing places. This project is planned so that all groups of people, especially in the Kramat district can use it so that it is not only a place to release fatigue but also a place to interact with each other to establish stronger relationships in the community so that it can be useful for the future. The community has also become aware of the impact of natural damage, so this project will be designed environmentally friendly. AbstrakKehidupan perkotaan identik dengan rutinitas dan kesibukan tinggi dimana persaingan antar individu masyarakat terus meningkat. Rutinitas dan kesibukan yang terus terakumulasi oleh setiap individu memicu kepenatan dan mengakibatkan sikap kerja/belajar yang kurang produktif. Third place hadir untuk menyeimbangkan kehidupan masayarakat diluar rumah dan tempat kerja. Dengan begitu, third place diperlukan dalam kawasan kota besar yang disesuaikan pula dengan kebutuhan masyarakatnya. Proyek ini mendukung keseimbangan hidup masyarakat di sekitar kelurahan Kramat, Senen dengan program – program yang sesuai kebutuhan. Program yang muncul sesuai kawasan Kramat yaitu ruang kreatif karena warga sekitar yang telah menjalani profesi  sebagai pengrajin ondel – ondel namun tidak tersedianya wadah untuk menyalurkan bakat tersebut. Metode perancangan meliputi teknik pengumpulan data melalui observasi dan wawancara dengan hasil yang diaplikasikan ke dalam metode perancangan tarnsformasi. Ruang Kreatif Kramat di kawasan Senen ini merupakan third place yang direncanakan untuk melayani kebutuhan masyarakat sekitar dalam bidang sosial dan kreativitas guna menjawab isu kehidupan perkotaan karena kesibukan sehari-hari. Proyek ini menyediakan beberapa fasilitas yang mewadahi kegiatan masyarakat pada pendidikan, tempat makan, dan tempat berkumpul/bersosialisasi. Proyek ini direncanakan agar semua golongan masyarakat terutama di kelurahan Kramat dapat menggunakannya sehingga bukan hanya sebagai tempat pelepas penat namun juga tempat untuk saling berinteraksi agar terjalin hubungan yang lebih kuat dalam masyarakat sehingga bisa berguna bagi kedepannya. Masyarakat pun telah menyadari dampak kerusakan alam maka proyek ini akan dirancang ramah lingkungan.